2020
DOI: 10.1002/bse.2591
|View full text |Cite
|
Sign up to set email alerts
|

Does financial development stimulate environmental sustainability? Evidence from a panel study of 115 countries

Abstract: This paper investigates the moderation effect of financial development (FD) on the environmental Kuznets curve (EKC). Using comprehensive panel data of 115 countries spanning the 1990–2016 period and dividing the countries into different income groups, the researcher found systematic differences in the relationship between significant indicators of environmental degradation and economic growth. More specifically, the interaction effect of FD on the relationship between gross domestic product (GDP) growth and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 93 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, in the high-and middle-income groups, financial development had a negative impact on the relationship between GDP and both CH2 and PM2.5 emissions. This result suggested that financial development can reduce environmental degradation without adverse effects on growth [27]. Ref.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Furthermore, in the high-and middle-income groups, financial development had a negative impact on the relationship between GDP and both CH2 and PM2.5 emissions. This result suggested that financial development can reduce environmental degradation without adverse effects on growth [27]. Ref.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The moderation of financial development was engaged for 115 countries to validate the EKC across different income groups of countries. The study results regarding the moderation of financial development revealed the observance of stronger EKCs across different income groups [87]. The effect/moderation of urbanization for validation of the EKC was used in the case of Turkey, and the study results indicated that the moderation of urbanization was observed in an inverted U-shaped EKC [88].…”
Section: Literature Reviewmentioning
confidence: 93%
“…When selecting a transportation mode, business organizations consider factors such as cost, time and vehicle capacity. Considering these factors, industrial management prefers the roadway mode of transportation as it offers better connectivity, cheap cost and easy availability (Uddin, 2020). While delivering the products in time, the transportation sector must also look after the carbon footprint released during product transportation.…”
Section: Problem Statement and Conceptualizationmentioning
confidence: 99%